Risk Mapping and Mitigation at CV Duta Globalindo Utama (The Indonesian Journal of Business Administration, 2014)
Abstract. Global population and urbanization growths increase the overall demand for lighting products. At the same time, resource scarcity and climate change become an increasing concern. CV. Duta Globalindo Utama is a company engaged in the field of products and services that offer the use of LEDs for the needs of the market share in Indonesia generally and in West Java especially, of which products and services include the use of LED lights and solar power applications for street lighting. The company wants to change its strategy and become a leasing company that targets buildings like apartment, office tower, shopping mall, and any other big places for their electricity needs. This strategy could bring big revenue for CV. Duta Globalindo Utama but also give a new risk on the leasing strategy. This study uses AUS / NZS framework, since the company is a trading company which has different clients that can continue throughout the year and occasionally needs adjustments in operational activities. There 21 risks in CV. Duta Globalindo Utama where 2 of them categorized as catastrophic risks and there are total 5 risks that must be handled because of its linkage with other risks. There are factors that considered important for CV. Duta Globalindo Utama to choose strategies to mitigate risk in CV. Duta Globalindo Utama which are cost, time, and conveniency. The criteria from those factors are divided to cost 20%, time 20%, and conveniency 60%. The alternatives that taken to mitigate the risks are stocking goods in the warehouse, providing samples of goods to the customers to eliminate the product specification error, creating website or online marketing, conduct training for employees, and making purchase in units of Rupiah to suppliers and receiving income in units of Dollar from customers. The alternatives are obtained to mitigate the five types of risks analyzed and finally also help mitigate other risks inherent to CV. Duta Globalindo Utama. These chosen alternatives should be done by CV. Duta Globalindo Utama in order to manage these risks and improve the company's performance.Â Keywords: CV. Duta Globalindo Utama, Leasing Strategy, Risk Management, Analytical Hierarchy Process, LED